Extreme genome scrambling in marine planktonic Oikopleura dioica cryptic species - Plessy, Charles; Mansfield, Michael J.; Bliznina, Aleksandra; Masunaga, Aki; West, Charlotte; Tan, Yongkai; Liu, Andrew W.; Grašič, Jan; del Río Pisula, María Sara; Sánchez-Serna, Gaspar; Fabrega-Torrus, Marc; Ferrández-Roldán, Alfonso; et al. (Genome Research, 2024)
Genome structural variations within species are rare. How selective constraints preserve gene order and chromosome structure is a central question in evolutionary biology that remains unsolved. Our sequencing of several genomes of the appendicularian tunicate Oikopleura dioica around the globe reveals extreme genome scrambling caused by thousands of chromosomal rearrangements, although showing no obvious morphological differences between these animals. The breakpoint accumulation rate is an order of magnitude higher than in ascidian tunicates, nematodes, Drosophila, or mammals. Chromosome arms and sex-specific regions appear to be the primary unit of macrosynteny conservation. At the microsyntenic level, scrambling did not preserve operon structures, suggesting an absence of selective pressure to maintain them. The uncoupling of the genome scrambling with morphological conservation in O. dioica suggests the presence of previously unnoticed cryptic species and provides a new biological system that challenges our previous vision of speciation in which similar animals always share similar genome structures.